Self-efficacy and turnover intentions: modelling of triple-serial mediators of work motivation, job satisfaction, and job burnout among early childhood special education teachers in Singapore - Kong, Wei Xuan (Nanyang Technological University, 2024)
With the increasing demand for Early Intervention Programme for Infants and Children (EIPIC) services, early childhood special education teachers face immense challenges, including high job demands and insufficient job resources. This may potentially lead to burnout and attrition. There have been little to no research that has investigated on the potential factors that may affect early childhood special education teachers’ burnout and attrition. This study aims to fill the gap by examining the relationship between self-efficacy in classroom management and turnover intentions through the mediation of work motivation, job satisfaction, and burnout among early childhood special education teachers in Singapore. The study employed a cross-sectional survey design with data from 166 early childhood special education teachers across four EIPIC organisations, employing self-report measures including the Perceived Self-Efficacy in Classroom Management scale, the Work Extrinsic and Intrinsic Motivation scale, the Teacher Job Satisfaction scale, the Maslach Burnout Inventory-Educators survey, and the Intention to Quit scale. Findings revealed that work motivation, teacher job satisfaction, and job burnout fully mediated the relationship between self-efficacy in classroom management and turnover intentions, indicating these factors sequentially influence teachers’ decision to leave. The study also emphasises the importance of enhancing job resources in early childhood special education teachers in Singapore. Job resources such as self-efficacy, intrinsic motivation, and teacher job satisfaction can help to mitigate burnout and turnover intentions. Limitations, implications of the findings of this study, and future direction are discussed.